The role of country of origin in product evaluations: Informational and standard‐of‐comparison effects - Li, Wai‐Kwan; Wyer, Robert S. (Journal of Consumer Psychology, 1994)
There are at least four different ways in which the country of origin of a product could affect its evaluations: (a) as a product attribute whose implications combine with other attributes to influence evaluations, (b) as a signal to infer more specific product characteristics, (c) as a heuristic (to simplify the evaluation task), and (d) as a standard relative to which the product is compared. The manner in which country of origin is used in evaluations was expected to depend on subjects' familiarity with the product being judged, the amount of attribute information available, the importance of the evaluation, and the order in which country‐of‐origin and intrinsic attribute information was received. In fact, country of origin appeared to function in three of the four ways considered, but there was little evidence that it served as a heuristic in any condition. Results confirm the need to consider the use of country‐of‐origin information in several different capacities simultaneously rather than assuming that its effects result from a single underlying process.